Sistem Penamaan Kampung Di Desa Banggae Kecamatan Mangarabombang Kabupaten Takalar - Kurnia Rahmadani; Johar Amir; Andi Fatimah Yunus (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract.This study describes the naming system and meaning of village names in Banggaae Village, Mangarabombang District, Takalar Regency. This type and research is descriptive qualitative research. The data of this research are the names of villages in Banggae Village. Sources of data obtained are elders and traditional leaders of Banggae Village. Data collection techniques used are observation, interviews, recording, and documentation. Data analysis techniques used are data reduction, data presentation, data verification, triangulation, and drawing conclusions. The results of this study are (a) the village naming system in terms of naming aspects. (b) based on morphological processes (c) based on endocentric phrase formation. The meanings of the names of the villages in Banggae Village are: (1) Jarannika means the horse ridden by the groom; (2) Banggae means fishing gear; (3) Tepok means a village with a broken bridge; (4) Tani means people whose occupations are farmers; (5) Kampung Beru means a village that has not been built for a long time; (6) Garassi means an event that causes people to die and their bodies are full of blood; (7) Bontoa means a large land; (8) Papekang Lambusuk means honest fish finder; (9) Paccendolang means a village that was once a place for making cendol; (10) Bolo means a resident whose occupation is milkfish cultivator; (11) Abdul Rahman Daeng Lili is a regional fighter in Banggae Village.Keywords: Village Name, Meaning and Village Naming System